The Alexandrite Effect - Jones, Dione Frances (Auckland University of Technology, 2014)
The Alexandrite is a novel about the interaction of three families affected by certain events which took place nearly a century ago. The discovery of a body in an English garden sets Pamela, a titled widow, on a world trip to discover the secret of the stone and mysterious letter which was on the body. The novel traces her search to find the reason for the stone and the letter being there, taking her from England to New Zealand, and out of the safe and privileged environment to which she is accustomed. The exegesis explores two main themes, both of which span the century of the novel’s story. The subject of adoption is an emotive one and one which has seen huge changes in the social approach and treatment. Post traumatic stress is a problem which affects more than just the victim, and this has not changed since World War I when it was barely acknowledged as a problem. Both of these subjects have been used in fiction throughout the century and the exegesis explores the differences over the time period. The changing times is reflected by the Alexandrite, the stone itself, which has the unusual characteristic of changing colour. This stone acts as a mainstay throughout the century while the families change around it and yet stay the same.
Keywords: Unusual stone; English title; Adoption; Post traumatic stress; Mystery; Family